VNTR-DAT1 and COMTVal158Met Genotypes Modulate Mental Flexibility and Adaptive Behavior Skills in Down Syndrome - del Hoyo, Laura; Xicota, Laura; Langohr, Klaus; Sánchez-Benavides, Gonzalo; de Sola, Susana; Cuenca-Royo, Aida; Rodriguez, Joan; Rodríguez-Morató, Jose; Farré, Magí; Dierssen, Mara; de la Torre, Rafael; , The TESDAD Study Group; et al. (Frontiers in Behavioral Neuroscience, 2016)
Down syndrome (DS) is an aneuploidy syndrome that is caused by trisomy for human chromosome 21 resulting in a characteristic cognitive and behavioral phenotype, which includes executive functioning and adaptive behavior difficulties possibly due to prefrontal cortex (PFC) deficits. DS also present a high risk for early onset of Alzheimer Disease (AD)-like dementia. The dopamine (DA) system plays a neuromodulatory role in the activity of the PFC. Several studies have implicated trait differences in DA signaling on executive functioning based on genetic polymorphisms in the genes encoding for the catechol-O-methyltransferase (COMTVal158Met) and the dopamine transporter (VNTR-DAT1). Since it is known that the phenotypic consequences of genetic variants are modulated by the genetic background in which they occur, we here explore whether these polymorphisms variants interact with the trisomic genetic background to influence gene expression, and how this in turn mediates DS phenotype variability regarding PFC cognition. We genotyped 69 young adults of both genders with DS, and found that VNTR-DAT1 was in Hardy-Weinberg equilibrium but COMTVal158Met had a reduced frequency of Met allele homozygotes. In our population, genotypes conferring higher DA availability, such as Met allele carriers and VNTR-DAT1 10-repeat allele homozygotes, resulted in improved performance in executive function tasks that require mental flexibility. Met allele carriers showed worse adaptive social skills and self-direction, and increased scores in the social subscale of the Dementia Questionnaire for People with Intellectual Disabilities than Val allele homozygotes. The VNTR-DAT1 was not involved in adaptive behavior or early dementia symptoms. Our results suggest that genetic variants of COMTVal158Met and VNTR-DAT1 may contribute to PFC-dependent cognition, while only COMTVal158Met is involved in behavioral phenotypes of DS, similar to euploid population.